Identification and biological activities of triterpenoid saponins from chenopodium quinoa - Woldemichael, Girma Moges; Wink, Michael (Journal of agricultural and food chemistry, 2001)
At least 16 saponins were detected in the seeds of Chenopodium quinoa. The 5 previously isolated major saponins, 3-O-β-d-glucuronopyranosyl oleanolic acid 28-O-β-d-glucopyranosyl ester, 3-O-α-l-arabinopyranosyl hederagenin 28-O-β-d-glucopyranosyl ester, 3-O-β-d-glucopyranosyl-(1→3)-α-l-arabinopyranosyl hederagenin 28-O-β-d-glucopyranosyl ester, 3-O-α-l-arabinopyranosyl phytolaccagenic acid 28-O-β-d-glucopyranosyl ester, 3-O-β-d-glucopyranosyl-(1→3)-α-l-arabinopyranosyl phytolaccagenic acid 28-O-β-d-glucopyranosyl ester, and the new saponin 3-O-β-d-glucopyranosyl-(1→3)-α-l-arabinopyranosyl phytolaccagenic acid were isolated and characterized using mainly NMR spectroscopy, mass spectrometry, and chemical methods. The antifungal activity against Candida albicans and hemolytic activity on erythrocytes of these compounds and derived monodesmosides were evaluated. Both bidesmosides and derived monodesmosides showed little or no antifungal activity, whereas a comparatively higher degree of hemolytic activity could be determined for monodesmosides. Keywords: Chenopodium quinoa; Chenopodiaceae; triterpene saponins; antifungal activity; hemolytic activity